Diversity of Useful Plants in the Coffee Forests of Ethiopia - Senbeta, Feyera; Gole, Tadesse Woldemariam; Denich, Manfred; Kellbessa, Ensermu (Ethnobotany Research and Applications, 2013)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> Plant use diversity and their forms of use and management were studied in four coffee forests of Ethiopia. A coffee forest is a segment of moist montane forest with occurrence of wild Arabica coffee populations. The present study was conducted in four forest fragments located in the southwestern and southeastern parts of the country. These forests represent three different indigenous ethnic groups that live in and around the coffee forests. On the bases of ethnobotanical and floristic studies, a total of 143 useful plant species representing 54 families were identified in all study areas. Nearly all species are native except one which is naturalized. The identified use categories include medicine, food, honey, material sources, social services, animal fodder and environmental uses. Overall, Yayu and Harenna shared a high number of useful plant species in common. Of the total, about 25 species (19%) were similarly used across three or more studied ethnic groups. The implication is that there is a difference between and among the four communities studied for general plant knowledge and uses. As observed, deforestation, over-harvesting, cultivation of marginal lands and overgrazing appear to be threatening the plant resources and their habitats in the studied areas. Ecosystem conservation will ensure in situ conservation of many useful plant species by applying sustainable harvesting methods for collecting plants for any type of use from wild habitats. <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –>